Assessment of process hygiene in take-away restaurants at gas stations in Serbia. (September 2019) - Jovanovic, J; Velebit, B; Nikolic, A; Branković Lazic, I; Babic Milijasevic, J; Mrdovic, B; Raseta, M
Abstract: The present study was conducted to assess the effectiveness of sanitary procedures on food contact surfaces and food handlers' hands in Serbian take-away restaurants at gas stations. For that purpose, a total of 2518 swabs of food contact surfaces and 709 food handlers' hand swabs were investigated for microbiological parameters of process hygiene. The results showed that 11.60% (292 of 2518) of swabs from food contact surfaces, and 16.50% (117 of 709) of swabs from the food handlers' hands were not compliant with the criteria in the self-control plans of the food business operators. Permanent, on-going training of employees on the proper implementation of sanitation procedures is of essential importance to implement effective good hygiene practices and hazard analysis and critical control point plans.